Prediction of Successful outcome of Labor Induction at Term by Transvaginal Sonographic Assessment of Cervical Length - Narissara Sanpanitchakit; Prisana Panichkul (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To examine transvaginal sonography assessment of cervical length (TVSCL) as a predictor of active phase of labor, successful vaginal delivery after labor induction, and to estimate the most useful cut-off point for cervical length (CL). Materials and Methods: A prospective cohort study was conducted in the Obstetrics and Gynecology Department of Phramongkutklao Hospital. Pre-induction cervical assessment was undertaken in 120 women with singleton pregnancy at 37-42 weeks of gestation who underwent induction of labor. All women were measured for CL using transvaginal sonography followed by pelvic examination for Bishop score (BS) assessment. Results: Successful induction of labor to active phase within 24 hours occurred in 84.1% of the subjects. The best cut-off point of CL for the prediction of successful labor induction to active phase within 24 hours was found to be 3.14 cm or less with a sensitivity of 73.3 %, a specificity of 78.9 %, as well as negative and positive predictive values of 35.7% and 94.9%, respectively. In addition, a 3.14 cm or less cut-off point of CL can be used to predict successful vaginal delivery with a sensitivity of 73.6%, a specificity of 50%, as well as a negative and positive predictive value of 52.3% and 71.8%, respectively.Conclusion: TVSCL was significantly associated with successful induction of labor to active phase within 24 hours and could be used as a predictor for successful induction to vaginal delivery with a 3.14 cm or less cut-off point of CL.